A Conversation with Felipe Criado Boado - Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2021)
Professor Criado-Boado’s work is wide-ranging, encompassing landscape archaeology, rural history, community science, the transfer of knowledge, and applied archaeology as well as heritage. He has done research on origins and developments of monumental architecture (field work in Spain, Portugal, UK, Chile, Argentina, Perú and Uruguay) and rock art (field experience and research on Spain, Portugal, Scandinavia, and Chile). His approach is linked to Interpretive theory, pointing out the conditions of possibility of archaeological and cultural knowledge and defining a systematic methodological framework to base archaeological interpretation.